2017
DOI: 10.18632/oncotarget.15690
|View full text |Cite
|
Sign up to set email alerts
|

The genetic variants in the PTEN/PI3K/AKT pathway predict susceptibility and CE(A)F chemotherapy response to breast cancer and clinical outcomes

Abstract: The PI3K/PTEN/AKT pathway play a critical role in balancing cell growth and death. Epidemiologic studies suggested that mutations of the PI3K/PTEN/AKT pathway genes are associated with cancer risk, yet no data are available for PTEN rs701848, PIK3CA rs2699887, and AKT1 rs2494752 polymorphism and breast cancer(BC) risk. A case-control study was performed in 920 BC patients and 908 healthy controls using the TaqMan assay method. Overall, individuals with PTEN rs701848 TC, CC and TC/CC genotypes showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…23,26 Tumors within the same molecular subtype are heterogeneous, and, although the reasons for these differences are not clear, recent evidence suggests that tumors in younger patients show higher expression of genes related to mammary stem cells and deregulation of mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) pathways, which can con-tribute to endocrine therapy resistance and chemosensitivity in ER-positive tumors. [27][28][29] Tumors with lower PR expression had a higher probability of achieving cCR. In fact, it has been shown that PR expression in ER-positive tumors is associated with less aggressive phenotypes, and that tumors with lower PR expression may be less dependent on ER pathway signaling and show upregulation of the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…23,26 Tumors within the same molecular subtype are heterogeneous, and, although the reasons for these differences are not clear, recent evidence suggests that tumors in younger patients show higher expression of genes related to mammary stem cells and deregulation of mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) pathways, which can con-tribute to endocrine therapy resistance and chemosensitivity in ER-positive tumors. [27][28][29] Tumors with lower PR expression had a higher probability of achieving cCR. In fact, it has been shown that PR expression in ER-positive tumors is associated with less aggressive phenotypes, and that tumors with lower PR expression may be less dependent on ER pathway signaling and show upregulation of the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We then assessed the remaining 53 reports in greater detail and excluded 35 articles that did not satisfy the eligibility criteria. Finally, 18 eligible case-control studies were included in our meta-analysis [ 20 – 37 ] (Figure 1 , Table 1 ). Moreover, we analyzed the data of each SNP independently in studies that investigated both rs701848 and rs2735343 SNPs [ 23 , 24 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our conclusion was different from Ma's study that investigated 206 ESCC cases and controls each and concluded that the rs701848 CC genotype was not associated with ESCC risk [ 24 ]. We performed subgroup analysis and did not find correlation between rs701848 and increased risk of other cancers [ 20 , 21 , 25 , 33 , 35 ]. Our results also showed that rs2735343 GG genotype was associated with increased cancer risk supporting Jang's [ 23 ] and Ma's [ 24 ] findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other lncRNAs have been described to participate in the regulation of the PI3K/Akt pathway. HOTAIR has been related to the methylation of the tumor suppressor gene PTEN , and it is well known that PTEN antagonizes PI3K . Therefore, loss of PTEN function allows the over‐activation of Akt.…”
Section: Lncrnas In Hallmarks Of Cancermentioning
confidence: 99%